Shortleaf Pine-Hardwood Mixture Development Through Ten Years in the Eastern Highland Rim of Tennessee - David Clabo; Puskar Khanal; Kevin Hoyt; Martin Schubert; Tony Garner; Stephen Peairs; Wayne Clatterbuck (Forest Science, 2026)
Management of pine-hardwood mixtures or mixedwood forest types is gaining interest in the southeastern United States where landowner objectives/attitudes, rising management costs, timber and carbon markets, and logging workforce factors may provide rationale for favoring these forest types. However, few studies in the region have documented long-term stand development patterns for pine-hardwood mixtures. The objectives of this study were to 1) evaluate ten-year survival and growth of planted shortleaf pine ( Pinus echinata ) following four site preparation and early release treatments, and 2) assess the associated natural regeneration composition and growth. A study area was established during 2013/2014 near Estill Springs, Tennessee. Fell-and-burn site preparation served as the control treatment, and three additional first and/or second year release treatments were tested. Shortleaf pine seedlings were planted at two spacings (3.6 × 3.6 m and 5.5 × 5.5 m). Results indicated a significant treatment x spacing interaction for shortleaf pine survival ( P = 0.01) with improved survival observed in the 3.6 × 3.6 m spacing herbicide release treatments. Average height growth was statistically significant ( P = 0.01) and greater in the herbicide-and-burn release treatment (8.1 m) compared to the control (6.8 m) and burn release (6.8 m) treatments. Invasive woody species were more common than other species groups, but they were significantly shorter than native woody species ( P < 0.001). Treatments that included herbicide release resulted in greater shortleaf pine survival and height growth. Oaks ( Quercus spp.) and other Pinus spp. were present in upper crown classes in the two herbicide release treatments after ten years, but additional management will be needed to suppress invasive woody species as these stands continue to develop.